Butcher & bolt : two hundred years of foreign failure in afghanistan - Loyn, David ([S.l.] : Hutchinson, 2008)
Afghanistan has been a strategic prize for foreign empires for more than two-hundred years. The British, Russians and Americans have all fought across its beautiful and inhospitable terrain, in conflicts variously ruthless, misguided and bloody. A century ago, the common sneer about how British soldiers treated Afghan tribesmen was that they would (3z(Bbutcher(3y (Bthem, then (3z(Bbolt.(3y (BThis violent history is the subject of David Loyn$1 (Bs magisterial book. He begins with the first British mission exactly two hundred years ago that ushered in a history of conflict littered with misunderstandings and broken promises, in which the British, the Russians and later the Americans, constantly under-estimated the ability of the Afghans and the power of the Frontier tribes. Butcher & Bolt brilliantly brings to life the personalities involved in Afghanistan$1 (Bs relationship with the world, chronicling the misunderstandings and missed opportunities that have so often led to war. Coming right up to date, it draws on David Loyn$1 (Bs unrivalled knowledge of the Taliban today and the forces that currently prevail in Afghanistan, to provide the definitive analysis of the lessons these conflicts have for the present day.s
International Edition.
Keywords: Afghan Wars; Afghanistan; International relations